ANALISIS ISI BERITA POLITIK JELANG PEMILIHAN PRESIDEN REPUBLIK INDONESIA TAHUN 2019 PADA SURAT KABAR DUMAI POS - Hesty Junika; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Content analysis is a research method using a set of procedures to make valid inferences from texts. Content analysis is a method for examining and analyzing a communication content within a certain time and space, with the aim to find out the tendency of messages conveyed both visible and hidden. The emergence of political news before the General Election (Election) is very influential on political decision making. Ahead of the Presidential Election day of the 2019-2014 period, various media in the country covered continuously in this regard, including Dumai Pos. So researchers are interested in analyzing the content of political news ahead of the 2019 Presidential Election published in the Dumai Pos newspaper to find out what the contents of the political news ahead of the presidential and vice presidential elections in 2019 were reported by Dumai Pos. This study aims to determine the number and percentage of political news about 2 presidential candidates ahead of the 2019 Indonesian presidential election in the Dumai Pos newspaper based on the unit of analysis.This research uses quantitative content analysis method with descriptive approach. This research is not intended to test a particular hypothesis or measure a variable, but merely describe the content in a story. The news samples examined were 24 news in the period March 23-April 13 2019.From the three news categories it can be concluded that in the Dumai Pos newspaper edition of March 25-April 13 2019 more news presents news of Prabowo-Sandi couples by 50% with 91.67% positive news and 8.3% negative news. While the Jokowi-Amin couple's news was 41.67% with 60% positive news and 40% negative news. Keywords: Content Analysis, Dumai Pos, Political News